2015
DOI: 10.3920/wmj2014.1799
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins and other fungal metabolites in grain dust from Norwegian grain elevators and compound feed mills

Abstract: Employees at grain elevators and compound feed mills are exposed to large amounts of grain dust during work, frequently leading to airway symptoms and asthma. Although the exposure to grain dust, microorganisms, β-1→3-glucans and endotoxins has been extensively studied, the focus on the mycotoxin content of grain dust has previously been limited to one or few mycotoxins. Our objective was therefore to screen settled grain dust from grain elevators and compound feed mills for fungal metabolites by LC/MS-MS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
3
29
0
Order By: Relevance
“…These concentrations are in accordance with data obtained for STC levels in dust from cereal storages in Belgium (Median 1.3 μg/g) (Tangni and Pussemier, 2007). Although Straumfors et al (2015) reported STC in 56% of dust samples taken from grain elevators and compound feed mills in Norway, the levels of STC were 10 to 100-fold lower than in our study. This may be due to colder environmental conditions in the Scandinavian region, which are not favourable for STC production in grain.…”
Section: Occurrence Of Stc In Dust From An Occupational and Living Ensupporting
confidence: 92%
See 2 more Smart Citations
“…These concentrations are in accordance with data obtained for STC levels in dust from cereal storages in Belgium (Median 1.3 μg/g) (Tangni and Pussemier, 2007). Although Straumfors et al (2015) reported STC in 56% of dust samples taken from grain elevators and compound feed mills in Norway, the levels of STC were 10 to 100-fold lower than in our study. This may be due to colder environmental conditions in the Scandinavian region, which are not favourable for STC production in grain.…”
Section: Occurrence Of Stc In Dust From An Occupational and Living Ensupporting
confidence: 92%
“…Although mycotoxin inhalatory toxicity and health effects in humans are under debate, studies have shown that mycotoxin inhalation may be at least 10 times more toxic than oral intake (Creasia et al, 1987(Creasia et al, , 1990. Taking into account the results presented in our study together with data on exposure of workers to flour dust (Zuskin et al, 1998) and recently reported possible health risks of various mycotoxin exposure in grain dust from Norwegian grain elevators and compound feed mills (Straumfors et al, 2015), we should focus on the possible health risks of inhalatory exposure to STC in occupational environments. Zuskin et al (1998) showed that in the flour processing area of a Croatian confectionary industry, the mean total flour dust was 12.3 mg/m 3 .…”
Section: Cytotoxic Potency Of Stc and Stc-producing Aspergilli -Possimentioning
confidence: 57%
See 1 more Smart Citation
“…Some candidate effect inducers may be a large number of microbial metabolites previously detected in grain dust. 35 It is also likely that some additives of animal feed could have effects.…”
Section: Discussionmentioning
confidence: 99%
“…Food monitoring studies investigate the prevalence and concentration of contaminants, including mycotoxins, in single food ingredients or foods (Lopez et al, 2016b;Schwartzbord and Brown, 2015;Straumfors et al, 2015). This increases the chance of detecting the mycotoxins under investigation.…”
Section: Food Monitoring Studymentioning
confidence: 99%